2018
DOI: 10.6028/nist.ir.8229
|View full text |Cite
|
Sign up to set email alerts
|

Community resilience planning guide for buildings and infrastructure systems: observations on initial implementations

Abstract: The National Institute of Standards and Technology (NIST) published the Community Resilience Planning Guide for Buildings and Infrastructure Systems (NIST SP 1190) in October 2015. The Guide describes a six-step process to develop a community resilience plan. The Guide was intended to be flexible, so that it could be used to create a standalone plan or to complement other planning processes by integrating resilience measures into longterm plans. Since the Guide's release, several communities have begun to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…All participants agreed that a comprehensive assessment of power outage resilience must balance performance-based metrics with capability-based criteria, recognizing the system's inherent network dependencies and how it interacts with extreme weather, which is consistent with the best practice literature (Cauffman, 2018). In addition, the agreedupon power outage resilience definition reflects the cyclical feedback and adaptive management principles inherent in emergency response planning.…”
Section: Qualitative and Quantitative Criteria Are Required For A Com...supporting
confidence: 53%
See 1 more Smart Citation
“…All participants agreed that a comprehensive assessment of power outage resilience must balance performance-based metrics with capability-based criteria, recognizing the system's inherent network dependencies and how it interacts with extreme weather, which is consistent with the best practice literature (Cauffman, 2018). In addition, the agreedupon power outage resilience definition reflects the cyclical feedback and adaptive management principles inherent in emergency response planning.…”
Section: Qualitative and Quantitative Criteria Are Required For A Com...supporting
confidence: 53%
“…Literature review and stakeholder focus groups identified that power outage resilience goals, reflecting the ambiguity of definitions, fell across multiple dimensions. Our analysis suggested that the certification process could be positioned across four considerations: intervention scale (Cauffman, 2018;Mathie and Cunningham, 2010;Shandiz et al, 2020), accessibility (Sharifi, 2016), life cycle (Gransberg and Ellicott, 1997;Driesen and Katiraei, 2008), and target audience (Zamuda et al, 2019). In consultation with MassCEC, we confirmed that these dimensions met its and the CLEAR program participants' goals, and for the pilot certification, we could focus on the design elements highlighted in Figure 2.…”
Section: Community Power Outage Resilience Goals Should Address Multi...mentioning
confidence: 93%
“…Compared with the street committee system ones, their planning modeled after the former Soviet Union, was logical and mixed land use (Chai and Zhang, 2010). This kind of planning provides easy access to daily facilities and significantly reduces traffic demand, thus maintaining a home -work balance.…”
Section: Characteristicmentioning
confidence: 99%
“…This kind of planning provides easy access to daily facilities and significantly reduces traffic demand, thus maintaining a home -work balance. Before 1978, the danwei community was an "acquaintance society," embracing a high level of social equality and social interaction and shaping the daily-life circle based on the danwei compound (Chai, 1996), thus promoting even development and a strong sense of place and belonging (Bjorklund, 1986). These circles were the ideal spatial organization to guarantee individual needs and collective consumption, enhancing residents' life quality in an era of relative scarcity (Lu, 2006).…”
Section: Characteristicmentioning
confidence: 99%